Antimicrobial photodynamic therapy potentiation by potassium iodide - Vieira, Cátia Sofia Silva (2021)
With the global increasing and spreading of antibiotic-resistant microorganisms, there is a need to develop strategies capable of inactivating plantonic and biofilm-forms of pathogenic microorganisms that causes untreatable and mortal infections. Antimicrobial photodynamic therapy (aPDT) is an alternative approach capable of combating microorganisms independently of their resistance profile. Althought this technique presents great results and advantages, the neutral and monocationic photosensitizers (PS) do not usually kill efficiently gram-negative bacteria and fungi, and their synthetic preparation are usually expensive and laborious. In this The results of these experiments demonstrated that FORM is efficient on inactivating planktonic forms of bacteria, fungi and viruses and that when combined with KI was clearly more effective to inactivate all the microorganisms. This combination allows also to destroy efficiently the preformed biofilms of bacteria and fungi and avoided also the formation of E. coli and S. aureus biofilms, contrarily to that observed with FORM but without KI. The use of FORM combined with KI allowed to reduce PS concentration and the treatment time which will promote to transpose the aPDT to the clinic or environment fields.context, it is needed to develop new approaches that can improve the antimicrobial effect of a PS and simultaneously to allow the decrease of the applied PS concentration and also of the treatment time. Recent studies have reported a enhancer effect on antimicrobial photoinactivation by the combined used of some PS and potassium iodide (KI), an inorganic salt. These studies have always shown potentiating effect of KI for the tested PS. The main goal of this work was, in a first phase, to achieve an insight into the KI potentiation effect on diferent groups of PS; tetraarylporphyrins positively charged at meso (including a formulation consisting of five cationic porphyrins - FORM) or β-pyrrolic positions and non-porphyrinic dyes, using a bioluminescent Escherichia coli as bacterial model. The results of these studies pointing out that the presence of KI can enhance the aPDT killing effect of some PS, but this enhancement is not general for all PS. The comparison of the obtained results with the ones from the literature allowed to confirm that the enhance effect of KI is related to the generation of 1O2 by PS, PS structure (charge number and charge position), aggregation behavior and its affinity for the external structures of the microorganisms. In a second phase, the aPDT effect of the FORM (easy to prepare when compared with their corresponding porphyrins that constitute the mixture in the pure form) and of its combined effect with KI (100mM) on planktonic and biofilm forms of a broad-spectrum of microorganisms. Therefore, this study was performed on the free and biofilms forms of gram-negative and gram-positive bacteria: E. coli resistant to chloramphenicol and ampicillin, and Staphylococcus aureus resistant to methicillin (MRSA), of the fungi Candida albicans as well as on the free-form of a T4 like bacteriophage as a model of human viruses.